Options for the control of elephants in conflict with people - Richard Hoare (Pachyderm)
Faced with a increasing elephant population in a decreasing range situation, at a time when a increasing amount of the management is taking place outside of protected areas, it is realized elephants are of considerable economic value at the same time they are a pest species. This paper focuses on an approach to dealing with the problem as a whole.